2014
DOI: 10.1144/geochem2012-177
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of handheld X-Ray fluorescence spectrometry in the exploration and development of carbonatite-related niobium deposits: a case study of the Aley Carbonatite, British Columbia, Canada

Abstract: This study evaluates the suitability of portable (handheld) X-Ray fluorescence spectrometry (pXRF) in the exploration for Aley-type ‘hard-rock’ (primary) carbonatite-hosted Nb deposits. The assessment consists of comparisons between: (1) results of pXRF analyses on selected pulp samples and results of analyses of the same pulps using traditional laboratory methods; (2) results of averaged, multiple pXRF spot field analyses performed directly on 10 to 15 cm long pieces of core (before pulverization) compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The potential of quick in situ analysis coupled with the instant display of results makes this technology particularly appealing for the mining industry. Most of the mineral resources-related pXRF projects have focussed on base and precious metals and have shown that this technology, when appropriately used, may yield data of sufficient quality for exploration and geochemical comparison [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of quick in situ analysis coupled with the instant display of results makes this technology particularly appealing for the mining industry. Most of the mineral resources-related pXRF projects have focussed on base and precious metals and have shown that this technology, when appropriately used, may yield data of sufficient quality for exploration and geochemical comparison [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, portable XRF spectrometers have proven suitable to detect REEs, Ta, and Nb in phosphates and carbonatites [13][14][15], W, Nb, Ta, La, Ce, and Zr in Sn-W ore-bearing granites [20], Ta and Zr in soil overlying granites [12], and P, Ba, Nb, V, Zr, and Y in various mafic to felsic igneous rocks [7,[21][22][23][24]. Consequently, critical elements can be detected and reliably quantified in geological materials devoid of interfering elements or when enriched.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that new deposits will be discovered as exploration methods for Nb and Ta are optimized. Some recent and significant breakthroughs include customizing and optimizing the use of portable X-Ray Fluorescence to provide sufficiently accurate and precise chemical analyses for specialty metals directly in the field (Simandl et al 2014), optimization of indicator mineral-based exploration methodology to detect Nb-Ta mineralization (e.g. Mackay and Simandl 2015;Mackay et al 2016), and the use of exploration biogeochemistry (Fajber et al 2015).…”
Section: New Exploration Methods and Other Developmentsmentioning
confidence: 99%
“…In one of a series of publications, Simandl et al 119 reported the use of hand-held XRF instrumentation for the exploration of primary carbonatite-hosted niobium deposits. In one of a series of publications, Simandl et al 119 reported the use of hand-held XRF instrumentation for the exploration of primary carbonatite-hosted niobium deposits.…”
Section: Geological and Climate Changementioning
confidence: 99%